Why did the wage share fall? Industry level evidence from Austria - Guschanski, Alexander; Onaran, Özlem (Wirtschaft und Gesellschaft, 2016)
There has been a significant decline in the share of wages in GDP in both developed and developing countries since the 1980s. This paper analyses the determinants of the wage share (labour compensation as a ratio to value added) using sectoral data for Austria, while also comparing our results with selected OECD countries. We compile a comprehensive sector-level dataset of nine OECD countries (Austria, Denmark, France, Germany, Italy, Spain, Sweden, the UK, the US) for the period of 1970 to 2011, which allows us to trace the developments in the wage share across high and low skilled sectors and within manufacturing and service industries. Our findings lend strong support to the political economy approach to functional income distribution. Technological change had an impact, especially in Austria, Italy, the US, but the effects are not robust with respect to the use of different specifications and the wage share in most countries in our sample appears to be driven by different variables reflecting the bargaining power of labour such as union density, adjusted bargaining coverage and government spending. The relevance of these variables differs considerably across countries, lending support to our approach of country specific estimations. We find that globalisation had a strong impact on the wage share in all countries. The effect of globalisation on the wage share was least strong in Denmark. In Austria, Germany, and to a lesser extent in the UK, the effect is due to outward FDI and intermediate import penetration which reflects the impact of international outsourcing practices. Intermediate imports penetrations had no significant impact in Spain while FDI played a smaller role in France and the US. Different institutional variables appear to be relevant for each country. Germany exhibits the most robust positive effect of union density on the wage share, while the decline in union density explains roughly 80 percent of the decline of the wage share in Austria. Conversely, collective bargaining coverage, together with social government spending, plays a more important role in France, the UK and the US. Financialisation had the most pronounced effect in Austria, the UK and the US, while it appears to be also relevant in Germany. We find mixed results for the effect of personal income inequality on the wage share. However, there is indicative confirmation for a negative effect in Austria, Germany, the UK and the US.